Sinatra up and running - Harris, Alan (O'Reilly Media, 2012)
Sinatra gives developers a small but powerful and scalable framework for building web applications with Ruby. This introduction gets readers started, helping them to build, install, and polish a first application. It also explores how Sinatra fits in the web application ecosystem, especially in comparison to its far larger cousin, Ruby on Rails.
Print version record
Keywords: Ruby (Computer program language); Web site development; Application software -- Development; Ruby (Langage de programmation); Sites Web; Développement; Logiciels d'application; Développement; Application software; Development